2015
DOI: 10.1371/journal.pone.0126795
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila Reporter for the Translational Activation of ATF4 Marks Stressed Cells during Development

Abstract: Eukaryotic cells have evolved signaling pathways that help to restore cellular homeostasis in response to various physiological or pathological conditions. ATF4 is a transcription factor whose mRNA translation is stimulated in response to stress-activated eIF2alpha kinases. Established conditions that activate eIF2alpha phosphorylation and ATF4 translation include excessive stress in the endoplasmic reticulum (ER) and amino acid deprivation. ATF4 is activated through a unique translational activation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…The last one overlaps Atf4 coding sequence in a different reading frame, therefore inhibiting its translation in the unstressed cells where upon ER stress, the main reading frame is translated [22]. In the reporter, Atf4 5’UTR is fused to dsRed ORF, then in stressed cells dsRed will be translated [36]. In control animals, no dsRed signal was detected (Figure 4A); however, when tcs2 (Figure 4B) or TCTC subunits were silenced (Figure 4C–E), a signal was detected, indicating that the UPR is active via the PERK/ATF4 pathway, confirming and extending our previous results for tcs3 and tcs5 [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last one overlaps Atf4 coding sequence in a different reading frame, therefore inhibiting its translation in the unstressed cells where upon ER stress, the main reading frame is translated [22]. In the reporter, Atf4 5’UTR is fused to dsRed ORF, then in stressed cells dsRed will be translated [36]. In control animals, no dsRed signal was detected (Figure 4A); however, when tcs2 (Figure 4B) or TCTC subunits were silenced (Figure 4C–E), a signal was detected, indicating that the UPR is active via the PERK/ATF4 pathway, confirming and extending our previous results for tcs3 and tcs5 [21].…”
Section: Resultsmentioning
confidence: 99%
“…Stocks were obtained from the Bloomington Drosophila Stock Center (BDSC) and the Vienna Drosophila Resource Center (VDRC) [25]. The Atf4 5’UTR::dsRed reporter is described in reference [36] and Xpb1::GFP is described in reference [37]. …”
Section: Methodsmentioning
confidence: 99%
“…Tunicamycin inhibits N-linked glycosylation in the ER, inducing a massive ER stress response through the UPR (29). This fivehour treatment is sufficient to significantly activate the UPR in the larvae, leading to developmental delay and lethality (15,30). We found that Ubi-superdeathi larvae are significantly more resistant to tunicamycin-induced lethality as compared to Ubi-control larvae ( Fig 5B, Table S1).…”
Section: Superdeath Regulates Er Stress-induced Apoptosis In Multiplementioning
confidence: 74%
“…crc is a bZIP transcription factor sharing sequence and functional homology with mammalian ATF4 (Hewes et al, 2000, Kang et al, 2015. In order to confirm activation of the ISR, we generated an antibody able to detect endogenous crc by western blot (Fig 2C and Supplementary Fig S2).…”
Section: Crc Regulates Wing Venation and Antagonises Mad Phosphorylationmentioning
confidence: 99%